2015
DOI: 10.1080/09593330.2015.1107623
|View full text |Cite
|
Sign up to set email alerts
|

Biofiltration technology for the removal of toluene from polluted air usingStreptomyces griseus

Abstract: Biofiltration technology has been recognized as a promising biotechnology for treating the volatile organic compounds (VOCs) present in polluted air. This study aims to investigate the performance of a biofiltration system of Streptomyces griseus sp. DSM-40759 immobilized on activated carbon (PICA S23) towards the adsorption and degradation of toluene vapour as well as to regenerate the activated carbon in situ. The batch studies were performed using nutrient agar medium and basal salt medium (BSM) for microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…This was expected, since several studies have reported that Streptomyces sp. may grow in PHP contaminated soils and are able to breakdown several recalcitrant petroleum hydrocarbons, such as phenanthrene, pyrene and naphthalene (Balachandran et al, 2012;Bourguignon et al, 2014;Mohamed et al, 2015). Interestingly, Gammaproteobacteria (represented mainly by the genus of Pseudomonas) was found in high proportions in both LC (60.69%) and HC (51.43%) sites.…”
Section: Associations Between Amf Spores and Microbial Communitiesmentioning
confidence: 99%
“…This was expected, since several studies have reported that Streptomyces sp. may grow in PHP contaminated soils and are able to breakdown several recalcitrant petroleum hydrocarbons, such as phenanthrene, pyrene and naphthalene (Balachandran et al, 2012;Bourguignon et al, 2014;Mohamed et al, 2015). Interestingly, Gammaproteobacteria (represented mainly by the genus of Pseudomonas) was found in high proportions in both LC (60.69%) and HC (51.43%) sites.…”
Section: Associations Between Amf Spores and Microbial Communitiesmentioning
confidence: 99%
“…All other chemicals were purchased from Merck (Germany). The mineral salt medium (MSM) used for irrigation in both biofilters was prepared according to Mohamed et al (2016). The airflow was supplied by a variable-speed model HVDLT-MK2 from SMAKN-CO England.…”
Section: Chemicalsmentioning
confidence: 99%
“…These efficiency values were maintained during the first phases since the BFs were aerated at night (during the experiments) for 12 h with the minimum flow and pollutant concentration. This can regenerate the removal of additional toluene (Mohamed et al 2016). Ondarts et al (2012) showed that the compost was a poor adsorbent (3 × 10 − 3 μg/g) when they were used for toluene treatment at a concentration of 81 μg/m 3 (Ondarts et al 2012).…”
Section: Toluene Removal Efficiency In Both Bfsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as a great many people invest the lion's share of energy inside, the indoor introduction assumes a critical part in the general individual presentation and along these lines in any well-being hazard evaluation. Activated carbon adsorption is the most effective technology for removing trace contaminants from both air and water (Mohamed et al, 2011(Mohamed et al, , 2015(Mohamed et al, , 2016a. On one hand, the utilization of activated carbons as adsorbents is restricted by the issue related to their recovery.…”
Section: Introductionmentioning
confidence: 99%